The Tourist Satisfaction Based On The Service Quality Of Tourism In Guizhou, China - Lim, Kim Yew; Gong, Wen; Wong, Chee Foo; Ng, Alex, Hou Hong; Jia, Simeng; Tan, Owee Kowang (INTI International University, 2019)
The purpose of this study is to explore the main factors affecting the service quality of the tourism industry in Guizhou. The research is quantitative based via questionnaire and responded by 404 toursts in Guizhou. Through Multiple Regression Analysis, accessibility, information, accommodation, and tourist attraction are found significant among Guizhou tourist with satisfaction. The main implication of the study is there is a need to explore the opportunity to ensure tourist satisfaction based on accessibility, information, accommodation, and tourist attraction. In addition, the main implication of this study is that provide theoretical contribution to academic. Because the survey uses different factors and methods to analyze the customer satisfaction from the previous research, it can provide some help and data support for future empirical research on tourism development in Guizhou Province. Meanwhile, this study combines tourism satisfaction with practical problems to provide data for helping the government to improve the service quality of the tourism industry